Lyophilized Human Cord Blood Leukoconcentrate to Treat Brain Ischemia in Rats - Lebedinets , Volodymyr; Ostankova , Ludmila; Bondarovych , Mykola; Lutsenko , Olena; Lebedinets , Dmytro; Grisha , Igor; Ostankov, Maksym; Parkhomenko , Kyrylo; Goltsev, Anatoliy (Problems of Cryobiology and Cryomedicine, 2022)
The paper outlines the experimental data on the impact of lyophilization on preservation of structural and functional characteristics of cells from human cord blood leukoconcentrate (HCBL). Lyophilization of HCBL was shown to ensure the preservation of cells with immune modulating potential in a heterogeneous population of HCBL. Lyophilized HCBL (lHCBL), to the same extent as cryopreserved one (cHCBL), revealed an equal immune correcting effect during ischemic brain injury in vivo in the experimental model of ischemic stroke (IS). The inclusion of lHCBL in therapy of brain ischemia demonstrated the improved indices of IFN-ү+ and IL-10+ spleen cells, adhesive and phagocytic activity of peritoneal cavity cells in rats with IS. The efficiency of using both lHCBL and cHCBL during IS may be associated with the implementation of therapeutic effect by presented among them cells and mediators, including multi-vector regulatory systems that maintain homeostatic stability of the body (immune, endocrine, nervous ones). Probl Cryobiol Cryomed 2022; 32(1): 044–057